PFKFB4 facilitates palbociclib resistance in oestrogen receptor‐positive breast cancer by enhancing stemness. Issue 1 (20th September 2022) - Wang, Sijie; Bei, Yuncheng; Tian, Qiang; He, Jian; Wang, Rui; Wang, Qiuping; Sun, Luchen; Ke, Jiangqiong; Xie, Congying; Shen, Pingping
Abstract: Background: ER + breast cancer (ER + BC) is the most common subtype of BC. Recently, CDK4/6 inhibitors combined with aromatase inhibitors have been approved by FDA as the first‐line therapy for patients with ER + BC, and showed promising therapeutic efficacy in clinical treatment. However, resistance to CDK4/6 inhibitors is frequently observed. A better understanding of the drug resistance mechanism is beneficial to improving therapeutic strategies by identifying optimal combinational treatments. Methods: Western blotting, qPCR, flow cytometry and a series of cell experiments were performed to evaluate the phenotype of MCF‐7/R cells. RNA sequencing, non‐targeted metabolomics, shRNA knockdown and tumour cell‐bearing mouse models were used to clarify the drug resistance mechanism. Results: Here, we found that ER + BC cells have shown an adaptive resistance to palbociclib‐induced cell cycle arrest by activating an alternative signal pathway, independent of the CDK4/6‐RB signal transduction. Continuing treatment of palbociclib evoked cellular senescence of ER + BC cells. Subsequently, the senescence‐like phenotype promoted stemness of ER + BC cells, accompanied by increased chemoresistance and tumour‐initiating potential. Based on transcriptome analysis, we found that PFKFB4 played an important role in stemness transformation and drug resistance. A close correlation was determined between PFKFB4 expression by ER + BC cells and cell senescence and stemness. Mechanistically, metabolomic profiling revealed that PFKFB4 reprogramed glucose metabolism and promoted cell stemness by enhancing glycolysis. Strikingly, diminishing PFKFB4 levels improved drug sensitivity and overcame chemoresistance during palbociclib treatment in ER + BC. Conclusions: These findings not only demonstrated the novel mechanism underlying which ER + BC cells resisted to palbociclib, but also provided a possible therapeutic strategy in the intervention of ER + BC to overcome drug resistance. Abstract : ER + breast cancer (ER + BC) cells have shown an adaptive resistance to palbociclib‐induced cell cycle arrest by activating alternative signal pathway, independent of the CDK4/6‐RB signal transduction. Continuing treatment of palbociclib evoked cellular senescence of ER + BC cells. Subsequently, the senescence‐like phenotype promoted stemness of ER + BC cells, accompanied by increased chemoresistance and tumour‐initiating potential. Based on transcriptome analysis, we found that PFKFB4 played an important role in stemness transformation and drug resistance. A close correlation was determined between PFKFB4 expression by ER + BC cells and cell senescence and stemness. Mechanistically, metabolomic profiling revealed that PFKFB4 reprogramed glucose metabolism and promoted cell stemness by enhancing glycolysis. Strikingly, diminishing PFKFB4 levels improved drug sensitivity and overcame chemoresistance during palbociclib treatment in ER + BC.